2001
DOI: 10.1177/146801730100100104
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Truth and Reflexivity

Abstract: • Summary: The authors argue that social work is as much a practical-moral activity as it is a technical-rational one. In order to pursue these themes, they explore the place of realist knowledge in social work and their alternative position on the complexities and ambiguities of practice. • Findings: Social work has long been troubled by the adequacy of its claims to professional status and about its possession of appropriate levels of knowledge and expertise. The dominant responses to this have been manager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(22 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…In order to be successful, the educational programs should combine, in a balanced manner, the theoretic elements with the practical approaches employed. Numerous researchers have attempted to illustrate in their studies the importance of using theory in social work education practice as a modality of enhancing the quality of social work practice [37,38]. Theory and practice in social work are interdependent.…”
Section: Methodological Aspects In Thementioning
confidence: 99%
“…In order to be successful, the educational programs should combine, in a balanced manner, the theoretic elements with the practical approaches employed. Numerous researchers have attempted to illustrate in their studies the importance of using theory in social work education practice as a modality of enhancing the quality of social work practice [37,38]. Theory and practice in social work are interdependent.…”
Section: Methodological Aspects In Thementioning
confidence: 99%
“…This places the onus on social workers to use their subjective, reflective skills to interpret and judge the relevance, reliability and weight of competing knowledge claims in particular situations or in relation to specific problems (Doherty & White, ; Sheppard, ; Sheppard, Newstead, Di Caccavo, & Ryan, ; Taylor & White, , ; White, ). More recently, claims for greater reflexivity have entreated social workers – practitioners and researchers – to develop greater awareness of their impact on the situations, people or phenomena with which they are dealing (Sheppard, ; Sheppard et al., ; Taylor & White, , ; White, ).…”
Section: Comparing 10 Models Of Knowledge Production In Social Workmentioning
confidence: 99%
“…This, then, could be viewed as an essential skill for effective decision making. It would seem to demand from practitioners the ability to be selfaware and refl ective, and, indeed, refl exivity is deemed a necessary skill by Taylor and White (2001). Willumsen and Skivenes 'Workers must convey, in honest, jargon-free terms, the reason for their involvement' 'The skill of applying intuition to judgements is not, addressed' 'New information could be ignored unless it supported their existing view' (2005) identifi ed additional dimensions to decision making; they analysed child protection processes in Norway and concluded that decisions may only be seen as legitimate if there has been proper collaboration with the affected parties.…”
Section: Decision-making Skillsmentioning
confidence: 99%